2020
DOI: 10.3390/ma13081980
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Carboxymethylcellulose Nanocomposite for Dressing Materials

Abstract: Sore, infected wounds are a major clinical issue, and there is thus an urgent need for novel biomaterials as multifunctional constituents for dressings. A set of biocomposites was prepared by solvent casting using different concentrations of carboxymethylcellulose (CMC) and exfoliated graphene oxide (Exf-GO) as a filler. Exf-GO was first obtained by the strong oxidation and exfoliation of graphite. The structural, morphological and mechanical properties of the composites (CMCx/Exf-GO) were evaluated, and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 57 publications
(69 reference statements)
3
12
1
Order By: Relevance
“…However, it is important to mention that the roughness of the surface will highly depend on the particular setting, specifically the viscosity and modification ratio of CMC used as well as the percentage of CMC dissolved in the solvent. In conditions similar to the ones used here, the same periodic pattern was observed in pure CMC film [ 71 ], although we could not find any data regarding films hydrolyzed by cellulase. We calculated the roughness of the surface and found that the Root Mean Square (RMS) of the pure CMC film is 17.9 nm ( Figure 7 A).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…However, it is important to mention that the roughness of the surface will highly depend on the particular setting, specifically the viscosity and modification ratio of CMC used as well as the percentage of CMC dissolved in the solvent. In conditions similar to the ones used here, the same periodic pattern was observed in pure CMC film [ 71 ], although we could not find any data regarding films hydrolyzed by cellulase. We calculated the roughness of the surface and found that the Root Mean Square (RMS) of the pure CMC film is 17.9 nm ( Figure 7 A).…”
Section: Resultssupporting
confidence: 73%
“…Using AFM, it was shown that the untreated CMC film had a regular pattern with small periodic holes about 10 nm in size ( Figure 7 A). AFM measurements on pure CMC films have been performed in the past, especially in the context of nanoparticles incorporation [ 71 , 72 ]. However, it is important to mention that the roughness of the surface will highly depend on the particular setting, specifically the viscosity and modification ratio of CMC used as well as the percentage of CMC dissolved in the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to mention that the roughness of the surface will highly depend on the particular setting, specifically the viscosity and modification ratio of CMC used as well as the percentage of CMC dissolved in the solvent. In conditions similar to the ones used here, the same periodic pattern was observed in pure CMC film 70 , though we could not find any data regarding films hydrolyzed by cellulase. On the contrary, the process of cellulose hydrolysis has been studied using AFM 72,73 , showing the directionality of hydrolysis in the contexts of cellulose fibers orientation.…”
Section: Resultssupporting
confidence: 71%
“…Using AFM, we could see that the untreated CMC film had a regular pattern with small periodic holes about 10 nm in size ( Figure 7A). AFM measurements on pure CMC films have been performed in the past especially in the context of nano particles incorporation 70,71 . However, it is important to mention that the roughness of the surface will highly depend on the particular setting, specifically the viscosity and modification ratio of CMC used as well as the percentage of CMC dissolved in the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy to highlight that Gram-negative bacteria are protected by a thin protective cell wall and an additional layer of lipoproteins and lipopolysaccharides (LPS), while Gram-positive bacteria are characterized by a thick layer of cell wall and are lacking of the additional LPS membrane. An LPS layer makes the Gram-negative strains much more resistant towards both natural and synthetic molecules [ 5 , 28 , 29 , 30 , 31 ], whose entrance into the cells is hampered by the hydrophobic nature of this additional layer. Actually, the infections due to Gram-negative bacteria are more difficult to eradicate [ 3 , 32 ].…”
Section: Resultsmentioning
confidence: 99%